Short-term outcomes of very preterm infants in a tertiary level neonatal intensive care unit in southeast region of Turkey - Bozkurt, Ozlem; Yucesoy Bagdiken, Ebru (Annals of Medical Research, 2021)
Aim: To examine the mortality and short-term outcomes of very preterm infants (≤32 weeks’ gestation) at Sanliurfa Training and Research Hospital.Materials and Methods: Very preterm infants hospitalized between September 2017 and February 2019 were retrospectively included in the study. Selected short-term outcomes were bronchopulmonary dysplasia, severe intraventricular hemorrhage, sepsis, periventricular leukomalacia, severe retinopathy of prematurity and necrotizing enterocolitis.Results: Within 18 months period 486 live born very preterm infants were included in the study. The mean birth weight was 1306 ± 459 g and gestational age was 29.1 ± 2.8 weeks. The antenatal steroid administration rate was 30.9%. The mortality rate was 30.5%. In the whole group survival rate without a major neonatal morbidity was 44.2%. The incidence of respiratory distress syndrome was 73.9%, patent ductus arteriosus was 20.4%, intraventricular hemorrhage grade III-IV was 7.6%, bronchopulmonary dysplasia was %16.9, periventricular leukomalacia was 7.6%, late onset sepsis was 42.6%, and culture proven sepsis was 14%, severe retinopathy of prematurity was 5.6%, and necrotizing enterocolitis was 2.1%. Conclusion: The mortality rate is higher than that of Turkey, while short-term morbidity rates are similar to the average in Turkey. The priority for Sanliurfa is to reduce the mortality rate in very preterm infants.
Keywords: Morbidity; outcome; survival rate; very-low birth weight; very preterm infant